2012
DOI: 10.1128/aac.06244-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization, Structural Studies, and In Vivo Activities of Anti-Chagas Disease Lead Compounds Derived from Tipifarnib

Abstract: g Chagas disease, caused by the protozoan pathogen Trypanosoma cruzi, remains a challenging infection due to the unavailability of safe and efficacious drugs. Inhibitors of the trypanosome sterol 14␣-demethylase enzyme (CYP51), including azole antifungal drugs, are promising candidates for development as anti-Chagas disease drugs. Posaconazole is under clinical investigation for Chagas disease, although the high cost of this drug may limit its widespread use. We have previously reported that the human protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Several factors could be in play. A majority of studies that previously reported successful clearance of murine T. cruzi infections by posaconazole employed mice in early acute phase, with treatment starting as early as 1 day after the infection (8,9,33,34,37,38). It is possible that T. cruzi parasites in longer-term infections respond differently to treatment with posaconazole than parasites in early acute infections.…”
Section: Discussionmentioning
confidence: 95%
“…Several factors could be in play. A majority of studies that previously reported successful clearance of murine T. cruzi infections by posaconazole employed mice in early acute phase, with treatment starting as early as 1 day after the infection (8,9,33,34,37,38). It is possible that T. cruzi parasites in longer-term infections respond differently to treatment with posaconazole than parasites in early acute infections.…”
Section: Discussionmentioning
confidence: 95%
“…Among them, CL-Brener (TcVI), whose complete genome sequencing was reported in 2005 (23), and Tulahuen (also TcVI), whose CYP51 gene we cloned and have been studying (24), are known to be drug sensitive, while there are other strains of the parasite that display medium [e.g., Y (TcII)] or high [e.g., Colombiana (TcI)] resistance to the current clinically available nitroderivative compounds (Bz and Nf) (20,25,26). Interestingly, this drug resistance appears to encompass antifungal azoles, including posaconazole (14,27).…”
mentioning
confidence: 99%
“…In these short-term in vivo experiments, we evaluated the ability of VT-1161 to suppress parasitemia during the acute phase of infection of mice with the Y strain of T. cruzi, because the Y strain is known to be naturally moderately resistant to nitro derivatives, such as benznidazole and nifurtimox (1), and has decreased susceptibility to the CYP51 inhibitors posaconazole (42,43) and VNI (44). Besides, infection of Swiss mice using 10 4 bloodstream forms of the Y strain of T. cruzi reaches peak parasitemia on day 8 (44), which allows the relatively fast selection of potentially promising compounds.…”
Section: Resultsmentioning
confidence: 99%